A Microbial Signature of Psychological Distress in Irritable Bowel Syndrome. Issue 8 (October 2018) - Peter, Johannes; Fournier, Camille; Durdevic, Marija; Knoblich, Lukas; Keip, Bettina; Dejaco, Clemens; Trauner, Michael; Moser, Gabriele
ABSTRACT: Objective: Irritable bowel syndrome (IBS) is associated with alterations along the brain-gut-microbiota axis. Previous studies have suggested a parallel segregation of microbial features and psychological burden in IBS. This study aimed at exploring the microbial correlates of psychological distress in patients with IBS. Methods: Forty-eight patients with IBS (Rome III criteria, M (SD) age = 42 (15) years, 35 female, 25 diarrhea-dominant, 5 constipation-dominant, and 18 alternating-type IBS) were assessed for psychological and clinical variables with validated questionnaires, fecal samples underwent microbial 16S rRNA analyses (regions V1–2). Microbial analyses comprised examination of alpha and beta diversity, correlational analyses of bacterial abundance and comparisons among subgroups defined by thresholds of psychological and IBS symptom variables, and machine learning to identify bacterial patterns corresponding with psychological distress. Results: Thirty-one patients (65%) showed elevated psychological distress, 22 (31%) anxiety, and 10 depression (21%). Microbial beta diversity was significantly associated with distress and depression ( q = .036 each, q values are p values false discovery rate–corrected for multiple testing). Depression was negatively associated with Lachnospiraceae abundance (Spearman's ρ = −0.58, q = .018). Patients exceeding thresholds of distress, anxiety, depression, and stress perception showed significantly higher abundances of Proteobacteria ( q = .020–.036). Patients with anxiety were characterized by elevated Bacteroidaceae ( q = .036). A signature of 148 unclassified species accounting for 3.9% of total bacterial abundance co-varied systematically with the presence of psychological distress. Conclusions: Psychological variables significantly segregated gut microbial features, underscoring the role of brain-gut-microbiota interaction in IBS. A microbial signature corresponding with psychological distress was identified. Clinical Trial Registration: ClinicalTrials.gov identifier NCT02536131, retrospectively registered. Abstract : Supplemental digital content is available in the text.